Inclusive and efficient value chains: Highlights, lessons learned, and priorities for one CGIAR - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
At the start of CGIAR Research Program on Policies, Institutions, and Markets (PIM) Phase 2 in 2017, and later during the priority-setting round in 2019, each of the PIM research areas (‘flagships’) formulated key research questions they aimed to answer and identified theories of change and pathways to achieve impact. In this series, we share highlights of what we have learned and achieved and suggest areas to be explored in the future.